The Effect of Servant Leadership, Political Skill and Job Crafting on Employee Performance With Organizational Commitment as a Mediation Variable - Fariana, Pitut; Mujanah, Siti; Shihab, Mohammad (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this study is to understand the impact of servant leadership, political skills, and job crafting on performance with organizational commitment as an intervention variable. The research uses a quantitative approach. The data analysis method used is Partial Least Square (PLS). Respondents of this study were Bawaslu employees of East Java Province as many as 98 samples from a total of 130 employees. The data collection instrument uses servant leadership, political skills, job crafting, organizational commitment, and employee performance variables using a Likert scale. From the results of the analysis, it was found that the variables of servant leadership, political skills, and job crafting has a significant impact on organizational commitment, as well as organizational commitment which has a significant impact on employee performance. So it can be said that all the hypotheses of this research are accepted. Servant leadership, political skills, job crafting, organizational commitment, and employee performance get very good perceptions, but in terms of servant leadership, it is expected that the leadership will provide orientation to the development of employee potential to be able to find unique values in each of them as capital in organizational development.